Emotional Intelligence Moderates the Effect of Case-Based Learning and Motivation on Entrepreneurship Understanding - I Made Sara (Budapest International Research and Critics University, 2022)
This study aims to examine the effect of the application of case-based learning methods and motivation on understanding entrepreneurship with emotional intelligence as a moderator. The population in this study were undergraduate students of Development Economics who had taken entrepreneurship courses at Warmadewa University. The sampling technique in this research is purposive sampling with certain criteria, such as students who have taken entrepreneurship courses. The research design is a survey research design by distributing questionnaires to respondents. Data analysis used moderated regression analysis (MRA). The results of this study indicate that the application of case-based learning and motivation methods has a significant positive effect on entrepreneurial interest, and it is proven that emotional intelligence is able to moderate the effect of applying case-based learning and motivation to understanding and interest in entrepreneurship.